Principles Of Development Of Creative Activity Of Primary Class Students In Tashkent Regional Universities - Mahmudova Z.Sh. (Euro Asian Journal Publishing, 2024)
The important difference between creative and independent thinking is that creative thinking is independent thinking, but not all active thinking and independent thinking in turn can be creative thinking
Keywords: creativity; creativityscience of logic